New stability criteria of continuous-time systems with delay - Zhu, Xun-Lin (2013)
This paper investigates the stability for continuous-time systems with interval time-varying delay via Jensen's integral inequality approach. By using a delay partition method, the sum of nonlinear coefficients in each subinterval is approximated with a nonlinear function rather than a constant. Combining with a reciprocally convex technique, new less conservative stability criteria are obtained in terms of linear matrix inequalities (LMIs). For finding appropriate parameters contained in the stability criteria, an optimal algorithm is provided. Numerical examples are given to illustrate the effectiveness of the proposed results.